Spectrophotometric Determination of Allopurinol by Oxidative Coupling Reaction Using 2-Nitrophenol Reagent in the Presence of N-Bromosuccinimide - Mohsen Hamza Bakr, Atiaf Nams Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
This research included the development of a fast, easy and sensitive spectrophotometric method for the determination of quantities of allopurinol. The method depends on the oxidative coupling reaction between allopurinol and the reagent 2-nitrophenol in the presence of N-bromosuccinimide, so the product is a yellow color soluble in water that gives the highest absorption at the wavelength 420 nm and it follows Beer’s law In a range of concentrations ranged from 24-2.4 μg/ml and the molar absorbance value was 9282.02 liters. ml-1.cm-1, the value of the correlation coefficient is R = 0.9963 and the Sandell index value has 0.0146 µg/cm2, the relative standard deviation value is 1.273 RSD%, and the detection limit is 0.6635 µg/ml. The proposed method has been successfully applied in the determination of allopurinol in its preparation. Pharmacist keywords: Allopurinol, oxidative conjugation, 2-Nitrophenol